Pengaruh Adiksi Game, Keaktifan Organisasi dan Pacaran terhadap Tingkat Stres dan Tingkah Laku Sosial pada mahasiswa FK UNAJA - Andre Budi (SCIENTIA JOURNAL, 2023)
This study aims to examine the influence of game addiction, organizational involvement, and romantic relationships on stress levels and social behavior among medical students at Adiwangsa University Jambi. Mental health issues among students are increasingly prevalent due to the complexity of academic and social demands. This research employs a quantitative approach with a cross-sectional design. Data were collected through questionnaires administered to 150 purposively selected respondents. Multiple linear regression analysis was used to evaluate both simultaneous and partial relationships among variables. The results indicate that game addiction has a significant positive effect on stress levels, while organizational involvement is negatively associated with stress and positively associated with social behavior. Meanwhile, romantic relationships showed varied effects depending on the intensity and quality of the relationship. These findings underscore the importance of managing non-academic activities to maintain students' psychosocial balance and highlight the need for campus-based interventions to promote mental health literacy.